A new blockchain and IoT based architecture of food safety system for confectionery supply chain in Industry 4.0 era - Kandasamy, Jayakrishna; Ethirajan, Manavalan; Agrawal, Tarun Kumar; Jagtap, Sandeep ; 0000-0001-5271-0192 (Applied Food Research, 2025)
The major challenges faced by confectionery supply chain are lack of information, traceability, managing the ownership of goods across supply chains, inability to track vendors in real-time. Blockchain and Internet of Things (IoT) in Industry 4.0 era help organisations to overcome these challenges by guaranteeing authentic information, real-time visibility, and transparency across the supply chain management. The extant literature has revealed that blockchain and IoT technologies are in their early stages of information management for the supply chain. This study explores the potential opportunities available with Blockchain and IoT in the confectionery supply chain. Utilising the inputs from the survey and interviews, the article identifies to present the gaps in the supply chain and proposes a new blockchain and IoT-based architecture of the food safety system for the confectionery supply chain. Typical blockchain architecture is designed for a food safety system, and the technical specifications required to implement blockchain are evaluated. Further, blockchain-assisted distribution information management is proposed to bring more visibility to the shipment of goods. Implications of deploying blockchain and IoT in the supply chain from a management perspective are discussed. The study distinguishes itself from existing literature in two ways: first, by introducing a tailored blockchain and IoT architecture specifically designed for food safety in the confectionery supply chain; and second, by demonstrating its practical implications in addressing real-time traceability, transparency, and operational efficiency in line with Industry 4.0 goals. This integrated approach helps organisations make informed decisions, reduce supply chain risks, and improve regulatory compliance across the confectionery value chain.